Gastrite crônica por Helicobacter pylori em pacientes com lesões pré neoplásicas: avaliação dos sistemas OLGA e OLGIM e desempenho de biomarcadores sorológicos na avaliação de risco de desenvolvimento de câncer gástrico - Maria Clara de Freitas Coelho (2019)
Introduction - Helicobacter pylori is recognized as a class I carcinogen for the development of gastric adenocarcinoma. Chronic atrophic gastritis is a precursor lesion, and its staging, according to the OLGA and OLGIM systems, aims to identify patients at increased risk of developing gastric cancer and facilitate its follow-up. Recently, it has been proposed to determine serum biomarkers [Pepsinogen I (PGI), Pepsinogen II (PGII), Gastrin 17 (G17) and anti-H. pylori antibodies as a noninvasive methodology for adenocarcinoma risk assessment in chronic H. pylori gastritis patients. There are no studies evaluating the usefulness and performance of these methodologies in the Brazilian population. This study aims to evaluate the concordance between the OLGA and OLGIM systems, as well as to study the biomarkers performance in patients with chronic H. pylori associated gastritis. Patients and Methods - Forty-one patients were recruited following chronic gastritis and the presence of pre-neoplastic lesions at histology and previously diagnosed with H. pylori infection (HC-UFMG Gastroenterology Outpatient Clinic). Patients underwent endoscopic examination with biopsies for pre-neoplastic staging lesions and blood collection for biomarkers serological analysis (PGI, PGII, PGI / PGII, G17 and anti- H. pylori antibodies). Results - Among the 41 patients, 28 were women and 13 men, ages ranged from 47 to 89 years old. By the OLGA system, we obtained: one patients staged as OLGA 0, seven OLGA I, 17 OLGA II, nine OLGA III and seven OLGA IV. By the OLGIM system, 14 patients were staged as OLGIM 0, five OLGIM I, 10 OLGIM II, 10 OLGIM III and two OLGIM IV. Regarding the histological staging among patients staged as low (OLGA / OLGIM 0, 1 and 2) and high risk (OLGA / OLGIM 3 and 4) for gastric cancer development, the agreement rate found between the classifications was 85, 4%. Biomarkers analysis of PGI, PGI / PGII and G17 showed sensitivity and specificity of 0,50 and 0,68; 0,06 and 0,84; 0,70 and 0,31 respectively. Conclusion - The histological classifications OLGA and OLGIM presented a good agreement rate among themselves. Simultaneous use of both histological classification systems was able to increase the identification of high-risk patients. Biomarker analysis was not effective in differentiating low to high risk patients in the studied population. Further studies are needed to validate its use in clinical practice in Brazil.